2021
DOI: 10.21203/rs.3.rs-803525/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Significantly suppressing ion migration in metal halide perovskites via trace of multivalent interstitial doping

Abstract: Cations with suitable sizes to occupy an interstitial site of perovskite crystals have been widely used to inhibit ion migration and promote performance and stability of perovskite optoelectronics. However, the interstitial doping accompanies inevitable lattice strain to impair long-range ordering and stability of the crystals to cause a sacrificial trade-off. Here, we unravel the evident influence of the valence states of the interstitial cations on their efficacy to suppress the ion migration. Incorporation … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…[100] Zhao et al revealed the effect of the valence state of interstitial cations on their inhibition of ion migration. [101] Through calculation, the interaction energy between Nd 3+ and the defect is the highest, and the interaction energies of Ca 2+ and Na + are slightly lower (Figure 7d). Considering the similar cation radius, the higher valence charge may contribute to the relatively strong interaction energy between Nd 3+ and the negatively charged intrinsic defects.…”
Section: Alkali Cationsmentioning
confidence: 95%
See 2 more Smart Citations
“…[100] Zhao et al revealed the effect of the valence state of interstitial cations on their inhibition of ion migration. [101] Through calculation, the interaction energy between Nd 3+ and the defect is the highest, and the interaction energies of Ca 2+ and Na + are slightly lower (Figure 7d). Considering the similar cation radius, the higher valence charge may contribute to the relatively strong interaction energy between Nd 3+ and the negatively charged intrinsic defects.…”
Section: Alkali Cationsmentioning
confidence: 95%
“…On the basis of the dominant role of ion migration at grain boundaries, it is crucial to suppress ion migration by passivating the defects at grain boundaries. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112] Liu et al proposed a strategy to passivate grain boundaries and inhibit ion migration by methimazole (MMI). [113] From the EDS results, it can be seen that the intensity of I in the initial aging device decreased from the HTL side to the ETL side, indicating that I migrated in the perovskite (Figure 9a).…”
Section: Grain Boundary Passivationmentioning
confidence: 99%
See 1 more Smart Citation